An appreciation of Vic Sidel's lifelong contributions to peace and social justice - Robert M. Gould (Social Medicine Publication Group, 2013)
This article presents a personal appreciation of the lifetime contributions of Victor W. Sidel, MD, to peace and social justice, exemplified by his work in Physicians for Social Responsibility and the American Public Health Association.